ANALISIS SEMIOTIKA PEIRCE DALAM PENGGUNAAN BAHASA EMPAT PILAR BERBANGSA DAN BERNEGARA MPR RI - Hastangka Hastangka; Armaidy Armawi; Kaelan Kaelan (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2018)
AbstrakPenggunaan istilah “Empat Pilar Berbangsa dan Bernegara” sebagai program sosialisasi MPR RI telah menimbulkan perdebatan. Istilah yang digunakan sejak tahun 2009 ini memberi dampak pada aspek linguistik di antaranya aspek sosiolinguistik, semantik, pragmatik, dan semiotika bahasa. Penelitian ini bertujuan mendeskripsikan persoalan semiotik penggunaan istilah Empat Pilar Berbangsa dan Bernegara oleh MPR RI, yakni Pancasila, UUD 1945, NKRI, dan Bhinneka Tunggal Ika. Data yang digunakan dalam penelitian ini berupa frasa Empat Pilar Berbangsa dan Bernegara. Pengumpulan data dilakukan menggunakan inventarisasi data, kategorisasi data, dan klarifikasi data. Metode untuk menganalisa penelitian ini memakai analisis semiotika. Hasil penelitian sebagai berikut. Pertama, istilah “Empat Pilar Berbangsa dan Bernegara” merupakan preposisi unik dan tidak lazim dalam konteks sosiolinguistik masyarakat Indonesia. Kedua, istilah Empat Pilar Berbangsa dan Bernegara yang mengkategorikan Pancasila, UUD 1945, NKRI, dan Bhinneka Tunggal Ika merupakan bentuk kesalahan semantik dan pragmatik. Ketiga, secara aturan penulisan simbol dan tanda, istilah tersebut bertentangan dengan hakikat kedudukan dan fungsi dari Pancasila, UUD 1945, NKRI, dan Bhinneka Tunggal Ika karena dijadikan sebagai satu varian yang sama, yaitu pilar. Keempat, penggunaan istilah Empat Pilar Berbangsa dan Bernegara telah mengacaukan sistem tanda dan simbol, terutama pada makna semiotis Pancasila, UUD 1945, NKRI, dan Bhinneka Tunggal Ika. Kata Kunci: Bahasa, Empat Pilar, Semiotik, Simbol. PEIRCE SEMIOTIC ANALYSIS IN THE USE OF THE FOUR PILLAR OF LANGUAGE NATION AND STATE OF MPR RI Abstract The application of the term “Four Pillars of the Nation and of the State” as the socialization program of MPR RI evokes debates. This term, which has been used since 2009, gives a significant impact in many aspects of linguistics, especially in the aspect of sosiolinguistic, semantic, pragmatic, and semiotics of language. This research aims to describe and analyze the problem of semiotics in the use of the Four Pillars of the Nation and of the State by the People's Consultative Assembly of the Republic of Indonesia. The “Four Pillars” referred to by the People's Consultative Assembly consist of Pancasila, 1945 Constitution, the Unitary State of the Republic of Indonesia, and Unity in Diversity. The research data is from the phrase “Four Pillars of the Nation and of the State” which is collected by using the data inventory, data categorization, and data clarification. Method of analyzing the data in this research is using semiotic analysis. Result: The results of this study indicate that: first, the term “Four Pillars of the Nation and of the State” is a unique and unusual preposition in the sociolinguistics context of Indonesian society. Second, this term which categorizes Pancasila, the 1945 Constitution, the Unitary State of the Republic of Indonesia, and Unity in Diversity becomes a mistake of the language terminology. It is because they are on the contrary to the semantic and pragmatic aspects. Third, based on the rules of writing the symbols and the sign, the Four Pillars of the Nation and of the State does contradict the position and function Pancasila, the 1945 Constitution, the Unitary State of the Republik of Indonesia, and Unity in Diversity originally have, as one exact same variant. Fourth, based on the semiotic aspects, the use of the Four Pillars of the Nation and of the State has disrupted the system of signs and symbols, especially the semiotic meaning of Pancasila, the 1945 Constitution, the Unitary State of the Republic of Indonesia, and Unity in Diversity. Keywords: language, four pillars, semiotics, symbol.